2008
DOI: 10.1007/s00415-008-0941-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of nocturnal sudden death in patients with multiple system atrophy

Abstract: Sudden death has been reported in patients with multiple system atrophy (MSA), although the frequency of this event has not been well delineated. We investigated the frequency and potential causes of sudden death in patients with MSA. During the 5-year observation period, 10 of 45 patients with probable MSA died. The causes of death included sudden death of unknown etiology (seven patients), aspiration pneumonia (one patient), asphyxia after vomiting (one patient), and lung cancer (one patient). The mean survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 14 publications
2
46
0
2
Order By: Relevance
“…Because patients with food stagnation within the esophagus did not necessarily report subjective symptoms other than dysphagia, evaluation of the esophageal phase on videofluorography is necessary. We previously demonstrated that patients with MSA frequently died suddenly during sleep and that upper airway obstruction might not fully explain the mechanism of sudden death [13].…”
Section: Discussionmentioning
confidence: 99%
“…Because patients with food stagnation within the esophagus did not necessarily report subjective symptoms other than dysphagia, evaluation of the esophageal phase on videofluorography is necessary. We previously demonstrated that patients with MSA frequently died suddenly during sleep and that upper airway obstruction might not fully explain the mechanism of sudden death [13].…”
Section: Discussionmentioning
confidence: 99%
“…The high frequency (71 %) of floppy epiglottis in MSA reported in this study could suggest that MSA patients are prone to present this type of epiglottic abnormality, probably related to an abnormal laryngeal tone. Since it has been reported that MSA patients could experience sudden death despite CPAP use [55], this study raises the possibility that downward displacement of the epiglottis by CPAP could cause upper airway obstruction and thus result in choking to death. However, floppy epiglottis should be not only observed under sedation with propofol, but also during physiologic sleep.…”
Section: Obstructive Apneamentioning
confidence: 87%
“…In MSA, tridor during wakefulness is a particularly harmful condition that can lead to subacute episodes of dramatic respiratory failure and death [52,Class III]. Also the presence of stridor during sleep is considered a life-threatening condition since it has been associated with decreased survival and higher rates of sudden death during sleep [54,Class III,55].…”
Section: Sleep-related Breathing Disorders Stridormentioning
confidence: 99%
“…Treatment, such as continuous positive airway pressure therapy or a tracheotomy, is effective. However, these treatments do not always prevent sudden death in patients with MSA, suggesting a mechanism such as central hypoventilation, other than upper airway obstruction, may play a role (Shimohata et al, 2008 …”
Section: Sleep Apnea Syndrome (Sas)mentioning
confidence: 99%